Extraction and fractionation of subproteome from root tips of Hyoscyamus albus: Sample preparation for H. albus root tip proteomics - Khandakar, Jebunnahar; Muktadir, Md Abdul; Islam, Md Shafiqul; Yamaguchi, Kenichi; Oda, Tatsuya; Kitamura, Yoshie (Journal of the Bangladesh Agricultural University, 2019)
Identification and quantification of different metabolites under stress, especially protein, is a vital way to understand plant adaptation mechanism. We established an efficient protein extraction method from the tiny amount (100 mg) of root tips of non-model medicinal plant Hyoscyamus albus, using bead-beating cell disruption, TRIzol extraction, and sequential chemical protein solubilization. H. albus is very well known for biosynthesized of different secondary metabolites like hyoscyamine, tropane alkaloids and scopolamine. Our method is rational for sample preparation even in small-scale proteomics of recalcitrant tissue and allows proficient, reproducible and impurity-free protein extraction. This method allows high-quality 2DE in mini-gel format (25 µg of protein/gel) for hydrophilic and hydrophobic sub-proteomes and is compatible to high-sensitive matrix-assisted laser/desorption ionization quadrupole ion trap time-of-flight (MALDI-QIT-TOF) mass spectrometry (MS). A protocol using TRIzol is more effective and reproducible to sequential chemical extraction of both hydrophilic and hydrophobic membrane proteins. We also demonstrated cell disrupted together with dithiothreitol (DTT) and polyvinylpolypyrrolidone (PVPP) is more useful to prevent polymerization of the phenolic compound than commonly used added DTT and PVPP with TRIzol reagent. Despite the unavailability of genomic sequence database, the efficacy of the protocol was also confirmed by MS/MS ion searches. <!--StartFragment --> J Bangladesh Agril Univ 17(4): 430–436, 2019